Dimensions of Human Sociality in the Qur'an - Rangkuti, Bima Wahyudin (Journal Analytica Islamica, 2024)
This research aims to examine the dimensions of human sociality in the Qur'an. Using the qualitative research method of literature study and based on various relevant data sources, the author carried out interpretations, reviews, and various comparative matters in order to explore the dimensions of human sociality itself. Based on the research carried out, certain verses were found in the Qur'an that seem to substantiate the human social dimension. These verses are Surah Al-'Alaq/96: 2, Surah Al-Baqarah/2: 213, and Surah Al-Hujurât/49: 13. Each of the verses studied substantiates human nature with its social authenticity.Penelitian ini bertujuan mengkaji dimensi kesosialan manusia dalam Al-Qur'an. Dengan menggunakan metode penelitian kualitatif studi pustaka, dan bertolak kepada berbagai sumber data yang berkenaan, penulis melakukan interpretasi, peninjauan, dan berbagai ihwal komparatif dalam rangka penelusuran terhadap dimensi kesosialan manusia itu sendiri. Berdasarkan penelusuran yang dilakukan ditemukan ayat-ayat tertentu dalam Al-Qur'an yang kiranya mensubstansikan dimensi kesosialan manusia. Adapun ayat-ayat tersebut adalah Surah Al-ʻAlaq/96 ayat 2, Surah Al-Baqarah/2 ayat 213, dan Surah Al-Hujurât/49 ayat 13. Di mana masing-masing ayat yang dikaji tersebut mensubstansikan natur manusia dengan kesejatian sosialnya.